2017
DOI: 10.7575/aiac.ijels.v.5n.2p.47
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Iranian ESP Learners’ Translation Ability and Resilience in Reading Comprehension

Abstract: The present study was an attempt to investigate the relationship between Iranian ESP Learners' translation ability and resilience in reading comprehension. More specifically, the study aimed to study the resilience cognitive and metacognitive effect on raising L2 reading comprehension through translation. Secondly, the study aimed at pursuing the views and attitudes to find out the extent to which resilience in reading comprehension can predict ESP learners' translation ability. In order to test the null hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
1
6
1
Order By: Relevance
“…At the present, it could be quite difficult to compare this specific correlation finding of the present study with those of other studies due to the scarcity of research in this area. However, the present study's specific finding could be interpreted, with cautions, as a further confirmation of several previous studies' findings on the positive relationship between resilience and several positive indicators of L2 learning such as motivated behaviours (Kim et al, 2018;Kim & Kim, 2020) and L2 achievements (Kamali & Fahim, 2011;Malekan & Hajimohammadi, 2017).…”
Section: Relationship Between Learners' Resilience and Sdl In Online English Classsupporting
confidence: 89%
See 1 more Smart Citation
“…At the present, it could be quite difficult to compare this specific correlation finding of the present study with those of other studies due to the scarcity of research in this area. However, the present study's specific finding could be interpreted, with cautions, as a further confirmation of several previous studies' findings on the positive relationship between resilience and several positive indicators of L2 learning such as motivated behaviours (Kim et al, 2018;Kim & Kim, 2020) and L2 achievements (Kamali & Fahim, 2011;Malekan & Hajimohammadi, 2017).…”
Section: Relationship Between Learners' Resilience and Sdl In Online English Classsupporting
confidence: 89%
“…In a similar vein, Kamali's and Fahim's (2011) study in the Iranian L2 context found that learners' levels of resilience had a significant effect on their reading ability of texts containing unfamiliar vocabulary items, suggesting the role of resilience in helping learners cope with difficult reading passages. Another study in Iran also found that learners' resilience in reading could predict their translation ability (Malekan & Hajimohammadi, 2017). Furthermore, a study by Oveisi and Nosratinia (2019) in an Iranian university found a significant, positive, and moderate correlation between learners' SDL and their resilience, r (122) = .42, p < .01.…”
Section: Literature Reviewmentioning
confidence: 90%
“…Stressing the role electronic learning plays in learning languages, Beatty and Ulasewicz (2006) Moreover, studies in the Iranian context have shown that that Iranian ESP students more than any other language skills need translation, reading, and writing (Amiri, 2000;Khoramshahi, 2015;Shahini, 1988). Translation of specialized English texts, however, is, as Malekan and Hajimohammadi (2017) holds, a problem to which Iranian EFL learners are frequently encountered. To cope with translation problems, medical students use paper dictionaries, offline electronic dictionaries on cellphones (mobile dictionaries), dictionaries on personal computers, and Internet-based or online dictionaries.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In the Iranian context, Kamali and Fahim (2011) reported that their participants' resilience significantly affected these participants' ability in comprehending texts containing unfamiliar vocabulary. In a similar vein, another study in Iran by Malekan and Hajimohammadi (2017) Abolmaali and Mahmudi (2013) found that these learners' resilience significantly predicted their academic achievement. In a similar vein, Najafzadeh et al ( 2019) also found a statistically significant, though weak, correlation between their 173 university learner participants' resilience and their achievement in English.…”
Section: Introductionmentioning
confidence: 72%
“…Though not as popular as SDL, resilience has also been investigated by various L2 research studies, mostly in the Asian context (e.g. : Danesh & Shahnaazari, 2020;Kim, Kim, & Kim, 2018;Kim & Kim, 2020Malekan & Hajimohammadi, 2017;Nguyen, Stanley, Stanley, & Wang, 2015;Subekti, 2021). In Korea, Kim and Kim (2016), involving 1620 secondary school learners, found that learners' resilience, seen from their persistence, could strongly predict their English as L2 proficiency and motivated learning behaviours.…”
Section: Introductionmentioning
confidence: 99%